Organizacija in negotovosti v digitalni dobi = Organization and uncertainty in the digital age: konferenčni zbornik / 37. mednarodna konferenca o razvoju organizacijskih znanosti, 21. - 23. marec 2018, Portorož, Slovenija = conference proceedings / 37th International Conference on Organizational Science Development, 21st - 23rd March 2018, Portorož, Slovenia (University of Maribor Press, 2018)
Organization and Uncertainty in the Digital Age : 37th International Conference on Organizational Science Development. The 37th Conference on Organizational Science Development is entitled Organization and Uncertainty in the Digital Age. The thread of the conference is the present position of organizations, strongly connected with the digitalization and coinciding fact of uncertainty being the only certainty. To achieve positive progress and results ensuring better and secure future, organizations and societies need to follow the trends. Contemporary time is a time of rapid digital advances as well as riots and crises, which often intervene in daily life of an individual, organization or society. Connecting the key elements of an organization; people, processes and informatics, the conference tends to expose the key issues and provide answers for the advances in organizational sciences. Based on past experiences in national and global danger or weakness, we are forming a future with a positive connotation. The conference aims to bulid on opportunities – opportunities for all of us, for the society and a generation of organizations and individuals, who will climb up the success scale. Based on the idea of the thematic concept of an organization, the strength and the direction of our discussions, knowledge and scientific results is primarily the identification, management and rehabilitation of uncertainty in the organization and society, and the majority of development trends related to the fundamental contemporary process – digitalization.